The effect of participatory action research on HPV primary preventive measures among in-school adolescents in Benue State, Nigeria - Evelyn Erdoo Orya; Comfort Msurshima Akume; Sunday Atobatele; Sidney Sampson; Esther Awazzi Envuladu; Hilary I. Okagbue (BMC, 2024)
Abstract Background Individuals with a higher level of awareness and knowledge of HPV are more likely to dispel misconceptions about HPV and reduce their likelihood of engaging in risky sexual behavior. Behavioural change can be achieved through interventions such as participatory action research (PAR), which has been applied in various contexts. Few studies have reported on the use of PAR in Nigeria. This study aims to utilise PAR as an intervention to increase HPV awareness, improve knowledge of HPV infection, and promote behavioural change for HPV prevention among young adolescents in Benue State, Nigeria. Methods The study design uses a school-based, pre-post intervention approach with a cross-sectional component. Study participants are young adolescents aged 10-19 years in selected co-educational secondary schools in three local government areas (LGAs) spread across the three senatorial zones in Benue State, Nigeria. Two-stage sampling was used to select the LGAs and schools, and the sample size was computed using the before and after implementation with some prior information from a previous study. Data on sociodemographic characteristics, HPV awareness and knowledge of infection and prevention, prevention practices, and willingness for HPV vaccination were obtained with a self-administered semi-structured questionnaire adapted from the Vaccination and HPV Knowledge (THinK) survey. The HPV Knowledge survey (New Zealand) was utilized to collect information from students at baseline and post-implementation after PAR intervention. The Wilcoxon Signed Test (WST) was used to investigate the significance of the median differences before and after the intervention. A p-value less than 0.05 or 0.001 was considered significant. Results A total of 548 adolescents were sampled before the intervention. After the intervention, the sample size decreased to 503, reflecting an 8% attrition rate. PAR effectively increased HPV awareness among the participants from 80.9% before the intervention to 99.8% afterward. The PAR led to a significant change in knowledge of HPV infection and primary prevention and an increase in perception of HPV primary prevention. decrease in misconceptions and risky sexual behaviours, increase in HIV screening tests, and increase in the willingness of participants to uptake the HPV vaccine. Among the measures of risky sexual behaviours was a decreased perception that having more than one sexual partner is not a risk factor for HPV after the PAR intervention. The number of participants in sexual relationships decreased from 84 (16.7%) at baseline to 37 (7.4%) post-implementation. The PAR also led to a decrease in the number of participants who reported having STDs. The Wilcoxon Signed test was further disaggregated based on sex (male and female), school funding type (public and private), and school class level (junior and senior). Conclusions PAR led to a significant increase in awareness and knowledge of HPV, knowledge of different aspects of HPV infection, and willingness to uptake the HPV vaccine. Additionally, the study has provided evidence that PAR interventions can be a viable tool in delaying sexual initiation and reducing sexual behavioural tendencies, especially in high-risk groups.